The Speech Politeness of Z-Generation in the Digital Era - Yustinah; Setiawan, Anjar; Sulthan, Faqih (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
The increasing integration of digital technology in higher education underscores the importance of speech politeness among Generation Z, particularly in online academic interactions. This study aims to explore the levels and characteristics of speech politeness exhibited by Generation Z students in digital contexts. A descriptive statistical method was used to analyze data collected through a Google Forms survey, involving 424 students from the Faculty of Economics—263 from Management, 145 from Accounting, and 16 from Agribusiness—who were enrolled in an Indonesian language course. The results indicated that 53.13% of students demonstrated awareness of speech politeness in the planning stage, 51.9% during implementation, and 56.9% in evaluation. These findings suggest a relatively balanced application of speech politeness across different stages of digital communication. Qualitative responses further revealed that students view speech politeness as beneficial for enhancing knowledge, skills, and attitudes in alignment with curricular goals. The study concludes that there is a harmonious relationship between theoretical understanding and practical application of speech politeness among Generation Z in the digital era.